Pengembangan Buku Saku Indonesiaku Kaya Budaya Berbasis Augmented Reality Dengan Assemblr Edu Untuk Kelas IV Sekolah Dasar - Meti Astuti Meti; Feri Ardiansah; Eka Wahyuningsih (Universitas Muhammadiyah Bangka Belitung, 2025)
This study is motivated by the suboptimal utilization of technology-based media in learning about Science and Social Science (IPAS), particularly in Indonesian cultural diversity (keberagaman budaya Indonesia). This research aims to develop a learning medium in the form of a pocket book titled My Indonesia is Rich in Culture, based on Augmented Reality (AR) using the Assemblr Edu application, which is feasible, practical, and effective for fourth-grade students at SD Negeri 52 Pangkalpinang. This study employs a Research and Development (R&D) approach using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The small-scale and large-scale trials involved 10 and 28 students, respectively. Data collection techniques included interviews, questionnaires, and tests. Quantitative data analysis was used, including feasibility assessments conducted by media and material experts. Practicality data were obtained from student and teacher questionnaire responses. Effectiveness data were derived from the analysis of pretest and posttest scores. The validation results from media experts showed a score of 70% (Valid), and from material experts, 100% (Very Valid). The small-scale trial yielded a practicality score of 95.75% (Very Practical), while the large-scale trial yielded 93.3% (Very Practical). The teacher response questionnaire scored 70% (Practical). The results of the paired sample t-test showed that the t-value was greater than the t-table (tcount=29.159 ttable 2.052), indicating that the alternative hypothesis (Ha) was accepted. It means that the development of the AR- based pocket book significantly influences learning outcomes related to the My Indonesia is Rich in Culture material.